Stock Price Determinants Of Listed Banks And Financial Institutions In Nepal - Bhandari, Ram Chandra; Thapa, Rajan Bikram; Acharya, Asha; Gupta, Surender Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2023)
Nepal Stock Exchange has strived to deliver an effective regulatory system and information transparency to acquire the confidence of the investors and convey the sufficient basis to analyze the data without anomalies. However, the investors in the stock market are still very few who are about negligible percent of total population in the nation. Government, banks, and financial institutions are not being able to play the prompt and desired role to create a stable share market with the expected outcome of the investors. Despite this, the investors have lack of knowledge both fundamental and technical regarding the capital market that causes them not to cut a good figure from the share market. The fundamental determinants and their types that affect the stock price are still matters of general thoughts in the existing stock market in Nepal. The several answers to the general thoughts become reliable references to the potential investors to make rational investment decisions. These all empower Nepal Stock Exchange authority and the administration of listed banks and financial institutions to skip any unexpected catastrophe, empower and control market strategies, strengthen the stock market industry. This research collected primary data using structured questionnaire from 111 respondents belonging to the market including investors, bankers, and experts of listed banks and financial institutions. It has used the analytical and descriptive research methodology to meet its prime objectives that were to identify determinants with their rank, of stock prices of listed banks and financial institutions listed in the Nepal Stock Exchange and deliver the ideas to the investors to consider the determinants for investment decision. It has observed the determinants of stock price of the banks and financial institutions as qualitative determinants and quantitative determinants. It has taken altogether 10 qualitative and 13 quantitative determinants including both specific and macroeconomic. In the research stock price and the determinants remained as dependent independent variables respectively. The result concluded that the goodwill, optimistic report of analysts, and positive views respectively are the major qualitative determinants with their ranks. Likewise, Dividend rate, earnings per share, and cash flow from operation respectively are the fundamental specific determinants with their rank. And the gross domestic product, interest rate, and inflation respectively with their rank are the major macroeconomic determinants. The recognition of the determinants and lack of analyzing experiences for investment decision on share have the great meaning for ensuring investors’ investment to generate desirable profit and keep their existence in the stock market in Nepal.